DSM-5 posttraumatic stress symptom dimensions and health-related quality of life among Chinese earthquake survivors. Issue 1 (1st January 2018) - Li, Gen; Wang, Li; Cao, Chengqi; Fang, Ruojiao; Liu, Ping; Luo, Shu; Zhang, Jianxin; Hall, Brain J.; Elhai, Jon D.
ABSTRACT: It has been well-documented that posttraumatic stress symptoms cause impairments in health-related quality of life (HRQoL). Until now we have little data on how DSM-5 PTSD symptom dimensions relate to different aspects of HRQoL. Clarifying this question would be informative to improve the quality of life of PTSD patients. This study aimed to investigate the effects of dimensions of a well-supported seven-factor model of DSM-5 PTSD symptoms on physical and psychosocial HRQoL. A total of 1063 adult survivors of the 2008 Wenchuan earthquake took part in this study nine years after the disaster. PTSD symptoms were measured by the PTSD Checklist for DSM-5 (PCL-5). HRQoL was measured by the Medical Outcomes Survey Short Form-36 (SF-36). The associations between PTSD symptom dimensions and HRQoL were examined using structural equation models. Dysphoric arousal symptoms were found to significantly relate to physical HRQoL. Other symptom dimensions were not associated with HRQoL. Our findings contribute to the relationship between DSM-5 PTSD and HRQoL, and carry implications for further clinical practice and research on trauma-exposed individuals.